1988
DOI: 10.1177/001440298805400408
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Classroom versus Resource Model: Academic Viability and Effectiveness

Abstract: This article compares student achievement data of the Integrated Classroom Model (ICM) to achievement data in resource room programs. Cost-effectiveness of the two programs is also compared. Comparison of pre- and postscores on the reading, math, and language subtests of the Woodcock-Johnson Psycho-Educational Battery indicated no significant differences in performance among elementary-school students with learning disabilities in integrated classrooms and resource classrooms. Comparisons of California Achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 9 publications
0
24
0
2
Order By: Relevance
“…Systematic searches of the literature reveal a plethora of conceptual or opinion articles on the REI, but only recently have data-based studies been reported that relate specifically to outcomes for students with specific learning disabilities (e.g., Affleck, Madge, Adams, & Lowenbraun, 1988;Bear et al, 1991;Cooper & Speece, 1990;Nowecek, McKinney, & Hallahan, 1990;Schulte, Osborne, & McKinney, 1990;. There also are conflicting findings.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic searches of the literature reveal a plethora of conceptual or opinion articles on the REI, but only recently have data-based studies been reported that relate specifically to outcomes for students with specific learning disabilities (e.g., Affleck, Madge, Adams, & Lowenbraun, 1988;Bear et al, 1991;Cooper & Speece, 1990;Nowecek, McKinney, & Hallahan, 1990;Schulte, Osborne, & McKinney, 1990;. There also are conflicting findings.…”
Section: Resultsmentioning
confidence: 99%
“…In the second, more common type of study, student comparisons are made across similar, matched inclusive and traditional/comparison schools. For both research designs, each study reviewed concluded either that inclusive school practices did not negatively affect general education students' academic achievement (Affleck, Madge, Adams, & Lowenbraun, 1988;Jenkins, Jewell, Leicester, Jenkins, & Troutner, 1991;Sharpe, York, & Knight, 1994;Willrodt & Claybrook, 1995), or that general education students' achievement increased in at least one academic area when inclusive practices were implemented (Fuller, Ronning, VanVoorhis, & Moore, 1993;Liddiard, 1991;Madden, Slavin, Karweit, Dolan, & Wasik, 1993;Saint-Laurent, Dionne, Giasson, Roger, Simard, & Pierard, 1998).…”
mentioning
confidence: 99%
“…Contrary to common assumptions, students with disabilities do not usually learn more in self-contained special education classrooms; equal or superior results are obtained when appropriate supports are provided in general education classrooms (Affleck, Madge, Adams, & Lowenbraun, 1988;Banerji & Dailey, 1995;Bunch & Valeo, 1997;Cole & Meyer, 1991;Freeman & Alkin, 2000;Fryxell & Kennedy, 1995;Hunt & Goetz, 1997;Ingraham & Daugherty, 1995;Logan & Keefe, 1997;Lipsky & Gartner, 1995;Madden, Slavin, Karweit, Dolan, & Wasik, 1993;McGregor & Vogelsberg, 1998;Schulte, Osborne, & McKinney, 1990;Waldron & McLeskey, 1998;Wang & Birch, 1984;Willrodt & Claybrook, 1995). Of course, educators are also concerned about the progress of students without disabilities; here the outcomes research is equally reassuring, with equal or superior academic, social, and behavioral outcomes for students without disabilities in inclusive general education classrooms compared to noninclusive classrooms (Holloway, Salisbury, Rainforth, & Palombar, 1995;Peck, Donaldson, & Pezzoli, 1990;Salend & Duhaney, 1999;Sasso & Rude, 1988;Sharpe, York, & Knight, 1994).…”
Section: Discussionmentioning
confidence: 94%